Understanding the Concept of Varnotpatti in Ayurveda - Bhaurao, Darokar Shrikant (International Journal of Innovative Research in Medical Science, 2017)
The concept of Varna has been adroitly described in the ayurveda texts. In Ayurveda Varna has considered as a mark of Health. The word Varna does not stands for complexion or colour of the skin but it comprises of a ample aspect of parameters useful for healthy and radiant skin. This Varna is influenced by a several circumstances before and after birth of human life. According to modern science, the skin complexion and colour of a person mainly depend upon the background of the ancestors and parents. The race to which the person belongs also matters upto great extent, because it is the genes that are mainly responsible. Various Ayurvedic and modern lexicons, journals, internet are used for present study. In classics role of diet, mahabhuta, shukra, ahara, vihara etc. is also explained for healthy skin.